Reframing Marie Antoinette: The Queen’s Transformation through Portraiture During Late 18th-Century France - Wang, Junyan (Transactions on Social Science, Education and Humanities Research, 2023)
This research paper delves into a certain time period of the captivating history of Marie Antoinette’s reign as the Queen of France from 1774 to 1793 through the lens of 18th-century portraiture. Amidst her declining image, her portrait artist Élisabeth Louise Vigée Le Brun emerged as a key influencer in salvaging Marie Antoinette’s tarnished reputation. After providing an overview of the socio-political context of the time period, a comparison is made between two portraits of the queen – Marie Antoinette en Chemise and Marie Antoinette and Her Children – that demonstrates the similarities and differences in the queen’s intentions and behaviour. Through a detailed visual analysis, we argue that the queen changes from a carefree spirit who exhibits limited adherence to French conventions to a responsible and mature woman and mother. In this transformation, she aligns herself with France’s traditions, showing her country that the people’s priorities and values come first. Related works and other scholarly opinions are embedded in this analysis to provide a variety of viewpoints and pinpoint the distinctive departure of this paper from their interpretations.